Intergenerational Scars? – Long-term Effect of Parental Unemployment during Depression on Socioeconomic Achievement - Karhula Aleksi; Lehti Hannu; Erola Jani (Turku Center for Welfare Research, 2025)
We studied the intergenerational impact of parental unemployment on the socioeconomic status of the children, seeking to determine whether or not the impact is reduced in the context of a profound economic depression employing data from one of the deepest depressions in the history of the OECD countries, the Finnish depression of the 1990s. We compare parental unemployment of children aged 12-18 both during a period of economic growth and depression and the duration of the unemployment, so as to identify the mechanisms behind the negative effects. The ISEI status of the children was observed when they were 30 years old. We used propensity score matching to analyze high-quality Finnish register data, comprising 15991 children. Our results show negative effects of parental unemployment that are not significantly reduced by occurring during a depression. In general, the results underline the importance of economic mechanisms behind the negative effects of parental unemployment.